(3OjhGf GHf MeOjSs - (3GdCROj GdUbdj, GHf MeOjS, CHh eMeO, YHO GdLHGQ Hf CHj HcQ Hf eMeO Hf MeOjS, J (B527 (3g`s ((3eMeO Hf WGgQ GdSeGhjs)
(3ChdgG (B:s
(3Edi eJi (B... (3ge CXeChfj Edi HQO GdXei adeG JQLd GdQoqj dj efg (B.. (3GdeGA (B** (3hNGdahfj ajeG cfJ Bedg efge hQH OhGA YGO cGdOGA (B...s
(3BNQgG (B:s
... (3hef Gdfhf (B: (3cCfeG GddjdI (B... (3hbO HOG ddYjf ahb (B.. (3hbO VefJ TYQG ef GdRYaQGf (B. (3Je HMeO Gddgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\274s
(3gOjI GdYGQajf (B1\499s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs